1994
DOI: 10.1139/f94-296
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Patterns of Chum Salmon in the Pacific Northwest

Abstract: We used starch-gel electrophoresis to examine over 13 000 adult chum salmon, Oncorhynchus keta, from 153 collections at 105 locations in Washington, Oregon, and southern British Columbia from 1985–92. We identified 39 variable loci and 36 monomorphic loci. In general, alleles that occurred at a frequency > 10% were found in all locations and were temporally stable within locations. Localized alleles usually occurred at a frequency <6%. Significant allele frequency differences were found among chum salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 25 publications
6
44
0
Order By: Relevance
“…Results of our genetic analyses are consistent with other allozyme studies of Pacific salmon (e.g., Utter et al 1989;Phelps et al 1994) in finding quantitative (frequency) rather than qualitative (fixed) genetic differences among populations. Nevertheless, moderate genetic differentiation is evident over the geographic area covered, as indicated by the G ST -value for the overall dataset (0.138).…”
Section: Genetic Analysessupporting
confidence: 91%
“…Results of our genetic analyses are consistent with other allozyme studies of Pacific salmon (e.g., Utter et al 1989;Phelps et al 1994) in finding quantitative (frequency) rather than qualitative (fixed) genetic differences among populations. Nevertheless, moderate genetic differentiation is evident over the geographic area covered, as indicated by the G ST -value for the overall dataset (0.138).…”
Section: Genetic Analysessupporting
confidence: 91%
“…Studies that used numerous allozyme loci as well as those that included samples from a wide geographic area were chosen. The data sets included two studies on Chinook salmon (O. tshawytshca Walbaum- Bartley et al 1992;Waples et al 2004), two on chum salmon (O. keta Walbaum- Phelps et al 1994;Wilmot et al 1994) and two on sockeye salmon (O. nerka Walbaum- Varnavskaya et al 1994;Wood et al 1994) (Table 1). Allozyme alleles frequencies were taken directly from the publications.…”
Section: Methodsmentioning
confidence: 99%
“…The Phelps et al (1994) chum salmon dataset showed two loci as being significantly high F ST outliers (sAAT-3 and mIDHP-1: Fig. 3A).…”
Section: Chum Salmonmentioning
confidence: 99%
“…Summer and fall runs of chum salmon also occur in the same rivers in Hood Canal and Puget Sound tributaries, (Johnson et al 1997). While Hood Canal summer chum salmon form an ESU separate from Hood Canal fall chum salmon, Puget Sound summer and fall chum salmon form an ESU together (Phelps et al 1994;Johnson et al 1997). Similar to Puget Sound chum salmon, Cowlitz summer chum salmon are most closely related to Cowlitz fall chum salmon.…”
Section: Broad-scale Population Structurementioning
confidence: 99%
“…Supplementation with non-native fish likely had little genetic effect upon remaining native chum salmon since juveniles were planted in tributaries where native runs were extinct (Johnson et al 1997) and the modest efforts (mean less than 500,000 fry per year) failed to restore populations. Further, genetic analyses (Phelps et al 1994) indicated that lower Columbia River chum salmon remain genetically distinct from other chum salmon in Washington State that had been planted as hatchery fish. Despite supplementation efforts and a moratorium on commercial exploitation implemented in the late 1950s, the chum salmon run remains around 2500 fish, roughly 3% of historical abundance (WDFW 2000).…”
Section: Introductionmentioning
confidence: 99%